Influence of organic and mineral fertilizers on number and physiological-biochemical activity of microorganisms of the gray forest soil - Малиновська, І. М.; Дегодюк, С. Е.; Ястремська, Л. С. (Problems of Environmental Biotechnology, 2017)
The state of microbial communities of gray forest soil was studied using mineral and organic fertilizers and their combinations. It is established that under the influence of fertilizers the number and physiological and biochemical activity of microorganisms of the main ecological-trophic groups change, the direction and intensity of agronomically valuable mineralization processes.